Interleaving Ontology Mapping for Online Semantic Annotation on Semantic Wiki - Ahn, Jinhyun; Jung, Jason J.; Choi, Key-Sun (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2008)
We have designed a system that automatically annotates language resources online by referring to the semantic correspondences obtained from ontology mapping methods. Every time user inputs a term, triplets are created using a predefined pattern-triplet mapping table. If an unidentifiable term has been entered (i.e., triplets could not be created from it), the system suggests alternative terms from a thesaurus. An ontology mapping task is to map the triplets into background ontologies, efficiently producing a semantic wiki page whose tag vocabularies are derived from the ontologies. In practice, collaborative editing is also available without leading to semantic inconsistency between editors, by allowing them to use their own background ontologies and aligning these different background ontologies.